Peoples' knowledge, attitude and use of over the counter drugs at Kawale township in Lilongwe. - Mvula, Doreen (Kamuzu University of Health Sciences, 2022)
The purpose of this study is to find out people's knowledge, attitude and use of over the counter drugs a Kawale Township. The study will use qualitative method in which an interview guide will be used. A sample of 20 Kawale residents will be recruited for the study. The participants will be interviewed using an interview guide. The data that will be collected will be analysed using content analysis. A letter asking for permission to conduct the study will be sought from the Research and publications committee of the Kamuzu College of Nursing. The letter will also be sent to the District Health Officer and the chief in Kawale. All the rights of the participants will be observed. Findings of the study will be communicated to KCN library, the District Health Officer and the chief of Kawale Township.